2018
DOI: 10.2147/ppa.s164160
|View full text |Cite
|
Sign up to set email alerts
|

Choosing the appropriate treatment setting: which information and decision-making needs do adult inpatients with mental disorders have? A qualitative interview study

Abstract: BackgroundDecisions on medical treatment setting are perceived as important but often difficult to make for patients with mental disorders. Shared decision-making as a strategy to decrease decisional conflict has been recommended, but is not yet widely implemented. This study aimed to investigate the information needs and the decision-making preferences of patients with mental disorders prior to the decision for a certain treatment setting. The results will serve as a prerequisite for the development of a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…First, the sample size was small and not randomly selected; gender distribution shows the rates observed in epidemiological studies (twofold in women), but most of the sample have secondary or university education, so it might be relevant to analyze the results in a sample with a lower education level. Nonetheless, results follow the line of those found in the literature [ 19 , 21 , 22 ]. Second, GAD diagnosis was not confirmed, and we cannot assure whether participants presented other anxiety or mental disorders.…”
Section: Limitationssupporting
confidence: 91%
See 1 more Smart Citation
“…First, the sample size was small and not randomly selected; gender distribution shows the rates observed in epidemiological studies (twofold in women), but most of the sample have secondary or university education, so it might be relevant to analyze the results in a sample with a lower education level. Nonetheless, results follow the line of those found in the literature [ 19 , 21 , 22 ]. Second, GAD diagnosis was not confirmed, and we cannot assure whether participants presented other anxiety or mental disorders.…”
Section: Limitationssupporting
confidence: 91%
“…The majority of patients preferred to share decisions with their clinicians, but they reported to be less involved than they would have liked to be. Similarly, the qualitative study by Kivelitz et al [ 22 ] found that patients with mental disorders wanted to be involved in the SDM process and to be informed with useful PtDAs about treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…Several antecedents that might become barriers to implement SDM in the mental health field appeared, but there were also attributes that could overcome these barriers. First, despite the concerns about users' capacity to participate in the decision‐making process, this review found the feasibility of SDM for adults with SMI, giving practical examples including those in acute wards (An et al, 2017; Hamann et al, 2011, 2017; Ishii et al, 2017; Kivelitz et al, 2018; Stacey et al, 2016; Velligan et al, 2016; Zisman‐Ilani et al, 2019). Using user‐friendly visualization could be a bridge to allay such concerns and worries about the users' capacity.…”
Section: Discussionmentioning
confidence: 99%
“…When reporting SDM as a multi-dimensional concept, there was greater variability in consumer preferences. The majority preferred to obtain information, discuss treatment options and express their views, and the minority want to make the final decision (Eliacin et al, 2015a;Fisher, Manicavasagar, Sharpe, Laidsaar-Powell, & Juraskova, 2017b;Kivelitz et al, 2018;Klingaman et al, 2015;Park et al, 2014;Velligan, Roberts, Sierra, Fredrick, & Roach, 2016). (Chong et al, 2013b;Shepherd et al, 2014;Younas et al, 2016).…”
Section: The Micro (Consumer) Levelmentioning
confidence: 99%